Come together: The importance of arts and cultural engagement within the Liverpool City Region throughout the COVID-19 lockdown periods - Chapple, Melissa; Anisimovich, Antonina; Worsley, Joanne; Watkins, Megan; Billington, Josie; Balabanova, Ekaterina (Frontiers in Psychology, 2023)
Introduction Arts and cultural engagement activities have long been found to support wellbeing within the general population. In particular, community arts and cultural involvement during the COVID-19 pandemic have been an invaluable source of mental health and wellbeing support for many individuals across the globe. The initial move to remote engagement following the first United Kingdom lockdown demonstrated the importance of hybrid provisions, with isolated and vulnerable individuals finding online provisions important for wellbeing. With restrictions on movement and service access in the United Kingdom having gradually eased from March 2021, it is now important to explore how individuals navigated the ability to engage with either remote or in-person provisions. The current study aimed to explore the impact of the COVID-19 pandemic on arts and cultural engagement during periods of restrictions and initial easings on movement within the Liverpool City Region. Method The study consisted of two waves of qualitative interviews within a broader longitudinal study. Twelve interviews were conducted during wave 1, which aimed to capture data during the initial COVID-19 lockdown period and the initial easing of restrictions. Eight of these participants were interviewed again for wave 2, which aimed to capture data during the winter 2020 lockdown period. Results Framework analysis revealed three overarching themes: (1) The Importance of Arts and Culture for Personal Enrichment, (2) Belongingness through Socialization, and (3) Transitioning and Adjusting Throughout the COVID-19 Pandemic. Discussion Findings presented in the current study provide further evidence of the value of arts and cultural activities in supporting wellbeing. Specifically, the current data emphasize the value of arts and cultural engagement throughout the COVID-19 pandemic and particularly during times of national restriction. Furthermore, the current study demonstrated that remote engagement provided important wellbeing support throughout the pandemic in a way that protected against mental health consequences, but with limitations on feelings of social connectedness within online environments. Amidst continuing risks from the COVID-19 virus and feelings of uncertainty, this study highlights the importance of hybrid provisions.